To solve the equation \(37x + 67 - 2x = 4\), we first simplify both sides.
- Combine like terms on the left side:
\[ 37x - 2x + 67 = 4 \]
This simplifies to:
\[ 35x + 67 = 4 \]
- Next, isolate the term with \(x\) by subtracting 67 from both sides:
\[ 35x = 4 - 67 \]
This simplifies to:
\[ 35x = -63 \]
- Now, divide both sides by 35 to solve for \(x\):
\[ x = \frac{-63}{35} \]
- Simplify the fraction:
\[ x = \frac{-63 \div 7}{35 \div 7} = \frac{-9}{5} \]
Thus, the solution is:
\[ x = -\frac{9}{5} \]
However, this value does not match any of the options you provided. Let's double-check the calculations:
Starting again from the equation:
\[ 37x + 67 - 2x = 4 \]
Combine like terms:
\[ (37x - 2x) + 67 = 4 \implies 35x + 67 = 4 \]
Subtract 67 from both sides:
\[ 35x = 4 - 67 \implies 35x = -63 \]
Divide by 35:
\[ x = -\frac{63}{35} \]
Which simplifies to:
\[ x = -\frac{9}{5} \]
Since none of the provided options match our result, it's likely that there may have been an oversight or misunderstanding in the question provided.
However, looking at the options given (22, 2, -2, -22), none of them match the correct answer which is \( -\frac{9}{5} \).
Thus, based on the solution obtained, the correct answer is not listed among the choices provided.